Electrical Line Fault Detection and Line Cut-Off Equipment and Control - Yakun Fu (Journal of Control Science and Engineering)
In order to locate the leakage fault location of low-voltage electrical lines, cut off the power supply of electrical lines, and ensure the safety and reliability of the power supply network, this paper proposes an electrical line leakage fault detection system based on a signal trigger. Based on the research on the current leakage protection system of low-voltage electrical lines, the author puts forward that the leakage current of the selected test analog trigger signal is not less than twice the maximum value of the normal leakage current of electrical lines and equipment with STC15F2K60S2 single-chip microcomputer as the control core. The experimental results show that 30 mA is preferred for the sensitivity of the leakage fault test signal. When the rated leakage action current is equal to or less than 30 mA, the protection action time is required to be less than 0.1 s, and when the rated leakage action current is greater than 30 mA, it is required to be less than 0.2 S. The device is a supplement to the traditional leakage protection device. According to the comparison between the indirect leakage detection and direct leakage detection results and the actual leakage position distance, the error is within 10%. It is proved that the system meets the actual needs and improves the protection performance of the leakage protection system of low-voltage electrical lines.